Aplikasi Kamus Pembelajaran Bahasa Jepang Pada Sistem Operasi Android Menggunakan Algoritma String Matching Knuth-Morris-Pratt - Yulia Darnita; Muhammad Husni Hidayat; Rozali Toyib; Ardi Wijaya (UNIVED Press, 2024)
As a globally advanced country, Japan attracts the interest of job seekers, especially from developing countries such as Indonesia. The primary motivation behind this interest is the opportunity to obtain better employment, higher income, and experience living in a culturally and linguistically different environment from their place of origin. One of the mandatory requirements for working in Japan is to have fluent Japanese language skills. However, challenges arise for prospective interns or job seekers who need to remain active in their current employment while awaiting their exam schedules or departure to Japan. To address this issue, a solution is needed that allows flexible Japanese language learning accessible anytime and anywhere, one of which is by creating an application that can be downloaded and installed on their smartphones. This application provides filtered Japanese vocabulary, eliminating the need for users to memorize all words like in conventional dictionaries, considering that some words may not be commonly used in daily situations. To enhance user convenience, the application is equipped with a word search function, facilitating the process of finding desired words. The search process in this application utilizes the Knuth-Morris-Pratt String Matching method, an efficient string matching algorithm for finding a specific pattern in a text. The application allows users to match inputted words with the available vocabulary database. This application is divided into two parts, namely the data input section and the output section used by users on their smartphone devices. The application provides various features to assist users in learning Japanese, such as vocabulary pages, conversations, and word searches. The use of the Knuth-Morris-Pratt (KMP) algorithm enables efficient and effective word searches in the vocabulary database. It is hoped that this application can help users in learning Japanese easily and effectively, both for academic and professional purposes.